MODERN RESEARCH TOOLS OF POLITICAL COMMUNICATION IN THE TRANSFORMING RUSSIAN SOCIETY - V. P. Miletsky; N. P. Pimenov (Дискурс)
The article describes modern research tools of political communication. Today political science is increasingly drawn to applied research methods: political monitoring, linguistic and psychological methods. Comparative analysis of these methods is to identify their strengths and weaknesses and to delineate the research scope for each of them. The integrated use of the above mentioned methods creates the possibility to conduct a full analysis of political communication in the Russian context, to identify their specific features and trends for further deployment.